2018
DOI: 10.1111/cpr.12492
|View full text |Cite
|
Sign up to set email alerts
|

AMOT130 linking F‐actin to YAP is involved in intervertebral disc degeneration

Abstract: This study showed that a mechanism by which Hippo pathway and F-actin synergize to modulate YAP activation and localization in the context of IDD and help to control NPCs proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Since the cytoplasmic vacuoles take up a large percentage of cell volume and NNPC are morphologically different from nonvacuolated CNPC [Hunter et al, 2003b;Kim et al, 2009b], it is not unreasonable to presume that by altering the organization and components of cytoskeletal proteins, these vacuous inclusions might modulate the Hippo-Yap signals in a similar manner as the cell contact or the high density attenuates cell growth. In support of this notion, we have revealed that the nuclear localization of YAP requires the integrity of the F-actin cytoskeleton in rat CNPC; moreover, LATS (large tumor suppressor homologs)-mediated YAP regulation by Hippo signals is also dependent on the integrity of F-actin, indicating that large cytoplasmic vacuoles and the altered cytoskeleton are closely related to regulation of Hippo-YAP and control cell proliferation in NNPC [Zhang et al, 2018].…”
Section: Evaluation Of the Hypothesismentioning
confidence: 56%
See 1 more Smart Citation
“…Since the cytoplasmic vacuoles take up a large percentage of cell volume and NNPC are morphologically different from nonvacuolated CNPC [Hunter et al, 2003b;Kim et al, 2009b], it is not unreasonable to presume that by altering the organization and components of cytoskeletal proteins, these vacuous inclusions might modulate the Hippo-Yap signals in a similar manner as the cell contact or the high density attenuates cell growth. In support of this notion, we have revealed that the nuclear localization of YAP requires the integrity of the F-actin cytoskeleton in rat CNPC; moreover, LATS (large tumor suppressor homologs)-mediated YAP regulation by Hippo signals is also dependent on the integrity of F-actin, indicating that large cytoplasmic vacuoles and the altered cytoskeleton are closely related to regulation of Hippo-YAP and control cell proliferation in NNPC [Zhang et al, 2018].…”
Section: Evaluation Of the Hypothesismentioning
confidence: 56%
“…In support of this notion, as rat IVD matures the cartilaginous matrix accumulates while the ratio of NNPC gradually decreases [Wang et al, , 2016Zhang et al, 2017Zhang et al, , 2018. Besides, compared to large and vacuolated NNPC, smaller nonvacuolated CNPC express higher levels of type I collagen, biglycan, and tissue inhibitor of metalloproteinases (MMP)-1 [Chen et al, 2006].…”
Section: Evaluation Of the Hypothesismentioning
confidence: 88%
“…Thus, it is possible that modular competition between PPxY motifs of filoviral VP40 and Amot for binding to the WW domain of YAP1 could impact several processes in the host cell including: 1) actin dynamics and polymerization, 2) tight junction formation and integrity, and 3) upregulation of cell proliferation genes (Fig 12). Our data indicate that competition for binding among YAP1/Amot/mVP40 complexes, as well as Amot's role in regulating F-actin dynamics at the plasma membrane [62,90], may both play a mechanistic role in impacting VP40-mediated egress.…”
Section: Discussionmentioning
confidence: 82%
“…Amot binds and sequesters YAP1 on both actin filaments and at cellular tight junctions (Fig 12) [59,60,62,64,65,[89][90][91][92][93][94]. The Amot/YAP1 complex may also enter the nucleus leading to upregulation of a set of genes that may be distinct from those upregulated by YAP1 alone [61,64,66].…”
Section: Discussionmentioning
confidence: 99%
“…YAP inhibition seems to occur by cell-to-cell contact in IVD cells [ 145 ]. Remarkably, while the expression of YAP decreases with age [ 146 ], YAP silencing was shown to promote NP cell senescence [ 145 ], which adds to the difficulty to duly apprehend the variation of disc cell regulation, upon multifactorial simulation and aging.…”
Section: Ivd Cell Activity and Molecular Biology In Health And Dismentioning
confidence: 99%